Stress fractures of the upper extremity - Brooks, A. A. (Clinics in Sports Medicine, 2001)
Stress fractures are common injuries in the athletic population. Although much of the published literature has focused on lower extremity stress injuries, these injuries also occur in the upper extremities. Stress injuries of bone result from repetitive loads smaller than would be required to cause an acute fracture. As bone is repetitively stressed, it behaves like any solid substance. If deformity occurs within its elastic range, it returns to its original configuration. If stressed into its plastic range, permanent deformity occurs, and microfractures propagate, causing structural failure and complete fracture of the involved bone. High clinical suspicion is required for diagnosis because of historical and physical features can be vague. Plain radiographs are often inconclusive, but bone scans and MR imaging usually help elucidate the diagnosis. Most upper extremity stress injuries will heal with nonoperative management. In rare situations these injuries can progress to nonunion, which requires surgical correction.